Real-time and reversible light-actuated microfluidic channel squeezing in dye-doped PDMS. Issue 18 (2nd April 2020) - Angelini, Angelo; Agero, Ubirajara; Ferrarese Lupi, Federico; Fretto, Matteo; Pirri, Fabrizio; Frascella, Francesca
Abstract : Reversible and real time light-triggered control of flows in a microfluidic azo doped device. Abstract : The azobenzene chromophore is used as a functional dye for the development of smart microfluidic devices. A single layer microfluidic channel is produced, exploiting the potential of a dye doped PDMS formulation. The key advantage of this approach is the possibility to control the fluid flow by means of a simple light stimulus. Furthermore, the deformation can be controlled in time, space and intensity, giving rise to several degrees of freedom in the actuation of the channel squeezing. A future perspective will be the implementation of the microfluidic platform with structured light, to have the possibility to control the flow in a parallel and reversible manner at several points, modifying the pattern in real time.